Spiritual intelligence as a moderator in the relationship between emotional intelligence and psychological well-being among Muslim healthcare workers in Klang Valley, Malaysia - Amran, Atiela; Nik Min, Nik Mohd Faris; Azhari, Nurul Nadhira Amalin; Abdullah Thani, Ayu Kamareenna (Journal of Islamic, Social, Economics and Development, 2025)
This study explores the role of emotional intelligence (EI) as an independent variable, spiritual intelligence (SI) as a moderating variable, and psychological well-being (PWB) as a dependent variable among muslim healthcare workers in government hospitals in Klang Valley, Malaysia. The study involved 208 respondents from a population of 271 public servants. The data collected was analyzed using SPSS, with descriptive statistics, reliability tests, and regression analysis applied. The results show that spiritual intelligence (SI)positively moderates the relationship between emotional intelligence (EI) and psychological well-being (PWB). This finding underscores the importance of EI in enhancing healthcare workers' well-being and highlights the critical role of spiritual intelligence in improving psychological outcomes in high-stress environments such as healthcare. This study contributes to the understanding of how emotional and spiritual competencies can foster better psychological health, providing valuable implications for managing healthcare personnel in public hospitals.